2016
DOI: 10.1016/j.chembiol.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for KDM5A Histone Lysine Demethylase Inhibition by Diverse Compounds

Abstract: SUMMARY The KDM5/JARID1 family of Fe(II)- and α-ketoglutarate-dependent demethylases removes methyl groups from methylated lysine 4 of histone H3. Accumulating evidence supports a role for KDM5 family members as oncogenic drivers. We compare the in vitro inhibitory properties and binding affinity of ten diverse compounds with all four family members, and present the crystal structures of the KDM5A linked Jumonji domain in complex with eight of these inhibitors in the presence of Mn(II). All eight inhibitors st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 43 publications
10
106
0
Order By: Relevance
“…These data suggest that both the demethylase activity and the demethylase-independent functions of KDM5s are required for modulating APA. Previous studies also showed that KDM5s have roles beyond their demethylase activity in cancer and development ( 36 , 48 , 61 , 62 ). Current KDM5 inhibitors are small molecules that inhibit KDM5 demethylase activity ( 48 , 49 , 63 67 ), and our results suggest that targeting other roles of KDM5A and KDM5B is also required to suppress the oncogenic roles of KDM5A and KDM5B.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These data suggest that both the demethylase activity and the demethylase-independent functions of KDM5s are required for modulating APA. Previous studies also showed that KDM5s have roles beyond their demethylase activity in cancer and development ( 36 , 48 , 61 , 62 ). Current KDM5 inhibitors are small molecules that inhibit KDM5 demethylase activity ( 48 , 49 , 63 67 ), and our results suggest that targeting other roles of KDM5A and KDM5B is also required to suppress the oncogenic roles of KDM5A and KDM5B.…”
Section: Discussionmentioning
confidence: 86%
“…As we have shown that Jhd2 promotes 3′UTR shortening of some genes in a demethylase-dependent manner in yeast, we further examined the contribution of the KDM5 demethylase activity to 3′UTR regulation in mammalian cells using a potent cell-permeable pan-KDM5 inhibitor, KDM5-C70 ( 48 , 49 ). Although KDM5-C70 treatment increased global H3K4me3 levels in MCF7 cells as expected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A nonselective inhibitory mechanism based on the ability of disulfiram to inhibit JARID1A’s PHD3 binding to H3K4me3 has also been described and used to inhibit growth of AMLs driven by a NUP98-JARID1A fusion gene [78]. Recent structural analyses identifying amino acid side chains and conformational plasticity unique to the JARID1 active sites have facilitated improvements in potency and selectivity of inhibitors [79, 80]. Presently the most notable result is CPI-455, a prototype tool compound with 200-fold selectivity for JARID1 over KDM4 demethylases and at least 500-fold selectivity over other KDM families [81].…”
Section: Targeting Jarid1 Functionmentioning
confidence: 99%
“…KDM inhibitors that occupy the αKG binding site are a promising new class of compounds that is currently under development and could be used to rescue the loss of H3K4me3 in MEN1 tumors. (Horton, et al 2016; Vinogradova, et al 2016). Conversely, as the loss of H3K4me3 at menin target genes was found to coincide with gain of H3K27me3, compounds inhibiting H3K27 methyltransferase activity could have similar effects on menin target genes affected by the loss of menin (Lin et al 2015).…”
Section: Relevance Of Menin Research For Men1-related Tumors and Potementioning
confidence: 99%